(untitled) (Pulse, 2023)
Stereotactic radiosurgery (SRS) has been widely used for the treatment of intracranial lesions. We have been doing SRS since March 2019. The unique ability of SRS to deliver higher focused dose to the smaller targets preferably in a single exposure in a convenient manner while sparing adjacent critical structures has made a more widely adopted treatment option. This case series is intended to show our institutional experience and procedural technique adapted for treating intracranial meningioma using SRS by Linear accelerators. We present five cases of intracranial meningioma. Four had Grade I meningioma and one patient with Grade III meningioma. One patient had radiological diagnosis only and treated with SRS. Two patients underwent gross total resection and SRS was prescribed on the event of recurrence. Rest two patients had recurrence/progression after subtotal resection and adjuvant radiation. The dose prescription ranged from 13 to 21Gy in one to three fractions which was determined by tumor volume, location, grade, proximity to critical structures, pre-existing neurologic impairment, previous treatment history, time to progression/relapse and the ideal balance of prescription dosage and expected problems. There were no acute side effects from any of the procedures. All five patients had improvement in clinical symptoms in the immediate post-SRS period. One patient who has two-year post-SRS revealed a significant regression in the size of the tumor. This case series summarizes the fact that SRS for intracranial meningioma is safe and effective treatment strategy when appropriate. Pulse Volume 12-14 2020-2022 p.40-52